Prognostic significance of CD163 expression in colorectal cancer stroma: a retrospective cohort study - Nauryzbay Imanbayev; Yerbolat Iztleuov; Arip Koyshybaev; Aigul Zhumasheva; Beibit Baizakov; Nurgul Kereyeva; Zhanna Satenova; Aigerim Imanbayeva; Anara Tulyayeva; Dinara Zholmukhamedova; Marzhan Aitmagambetova; Azamat Zharylgapov (Medicinski glasnik, 2025)
Aim: Colorectal cancer (CRC) ranks among the leading causes of cancer-related mortality worldwide, with significant incidence and mortality rates recorded in Kazakhstan. CRC poses a substantial healthcare burden, prompting investigations into novel prognostic markers. Aim: This study investigates the prognostic significance of CD163 expression in patients with colorectal cancer. Methods: This retrospective cohort study was conducted in Aktobe, Kazakhstan, utilizing tissue microarrays from 175 patients diagnosed with Tumor, Node, Metastasis (TNM) stage I-IV colon adenocarcinoma. CD163 expression was assessed through immunohistochemistry. Kaplan-Meier survival analysis was employed to estimate 5-year overall survival, defined as the interval from diagnosis to death or last follow-up. Cox proportional hazards models were used to evaluate the relationship between CD163 expression levels and survival outcomes. Results: High CD163 expression was linked to advanced disease stage of colorectal cancer (p < 0.001), lymphovascular invasion (p < 0.001), perineural invasion (p < 0.001), and Collagen I>30%, A type (p<0.001). CD163 infiltration was a negative prognostic factor for colorectal cancer patients, with higher risks of death in the high CD163 expression group compared to the low CD163 group (HR=5.769, 95% CI 3.194 - 10.42, p<0.001). Conclusion: The findings highlight CD163 as a potential prognostic biomarker in CRC, warranting further investigation into its mechanistic role and therapeutic implications.
Keywords: adenocarcinoma; biomarkers tumor; immunohistochemistry; survival analysis; tumor microenvironment